Socialization of People's Business Credit Policy to the Small and Medium Industries of Metro City Blacksmiths - Yuditya Wardhana; Syeni Rakhmadani; Ari Gusnita (LPM Universitas Pasundan, 2022)
The impact of the Covid 19 pandemic in 2020, Indonesia recorded a drastic deflation or decrease of -2.07%. The Small and Medium Industry (IKM) is one of the sectors that has been affected. The main obstacle experienced by SMEs is capital. Responding to these problems, the government has actually issued a policy on People's Business Credit which provides convenience and low interest. Its implementation is regulated in the Regulation of the Minister of Economic Affairs of the Republic of Indonesia Number 1 of 2022 concerning Guidelines for the Implementation of People's Business Credit, but there are still many people who do not understand and have access to this policy, one of which is the Blacksmith IKM actors in Metro City. This Community Service was held on November 1, 2022 at the Grand Venetian Hotel Ballroom through outreach and discussion. The purpose of this service is that the Blacksmith IKM actors can take advantage of the KUR program so that their businesses can develop more.